2015
DOI: 10.1021/ma502147m
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Highly Ordered Sodium Alginate/Montmorillonite Bionanocomposites

Abstract: A highly ordered alginate/montmorillonite bionanocomposite structure is presented. The alignment of the bionanocomposites has been determined by environmental scanning electron microscopy (ESEM) and wide-angle X-ray scattering (WAXS). The ESEM micrographs show a high inplane orientation of the bionanocomposite, while 2D X-ray scattering images show a clear angle dependency that confirms preferential orientation of montmorillonite (MMT) platelets. The order parameter (⟨P 2 ⟩) was calculated from azimuthal inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 28 publications
5
55
0
Order By: Relevance
“…We find an increase in the elasticity of the gel structure by addition of the Na-MMT platelets up to 80 wt.% Na-MMT, which we believe to be due to an increased level of interaction in the gel network. This gel formation, we propose, is responsible for the later development of the highly ordered nanostructure, which is achieved during water evaporation, as reported previously 9 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We find an increase in the elasticity of the gel structure by addition of the Na-MMT platelets up to 80 wt.% Na-MMT, which we believe to be due to an increased level of interaction in the gel network. This gel formation, we propose, is responsible for the later development of the highly ordered nanostructure, which is achieved during water evaporation, as reported previously 9 .…”
Section: Discussionsupporting
confidence: 82%
“…Using these biopolymers the concentration range of clay that can be successfully incorporated increases dramatically, with materials displaying unique properties, such as high level of alignment, and high volume fraction of the filler, which may result from favorable interaction between the biopolymer and the clay. All of the mentioned bio-nanocomposites have been produced via water casting of the biopolymer clay suspension 6,7,8,9 . Due to the nanostructure and the high volume fraction of the clay, these materials display superior mechanical and transport properties, when compared to conventional…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a difference of three orders of magnitude compared to the moduli of high performance (E‐glass/carbon) which implies that the mechanical properties of the compartmented fibers need to be significantly enhanced before they can contribute to the overall properties of structural composite materials. Zlopasa et al found that modulus of alginate films can be drastically increased when higher levels of MMT doping, up to 80 wt%, are used . However, as it was found that with increasing MMT concentration the coagulation speed decreases, it was impossible to spin high quality fibers with MMT concentrations higher than 20 wt% with the parameters used in this study.…”
Section: Resultsmentioning
confidence: 71%
“…Compartmented fibers were spun from an emulsion of healing agent and a solution of 6 wt% sodium alginate in de‐ionized water based on a methodology that is described in previous work . In order to reinforce the fibers, the sodium alginate solution was mixed with a 3 wt% MMT solution for 24 h at 300 rpm using a magnetic stirrer following the approach reported by Zlopasa et al to obtain a homogeneous dispersion . In this way solutions were prepared with 0, 10, and 20 wt% of MMT relative to the amount of sodium alginate.…”
Section: Methodsmentioning
confidence: 99%
“…Alginate, a seaweed-derived linear unbranched polysaccharide containing repeating units of 1,4-linked α-L-guluronic acid and β-Dmannuronic acid, is one of the most common natural materials used to fabricate alginate-based and composite materials. [18][19][20] In addition, alginate-based materials are natural, inexpensive, nontoxic, nonvolatile, and thermally stable. Gelling using divalent metal ions is widely applied in the medical field.…”
Section: Introductionmentioning
confidence: 99%